ОБРАЗОВАТЕЛЬНЫЙ ПОТЕНЦИАЛ НАЦИОНАЛЬНЫХ ПРИРОДНЫХ ПАРКОВ (НА ПРИМЕРЕ БАЯНАУЛЬСКОГО ГОСУДАРСТВЕННОГО НАЦИОНАЛЬНОГО ПРИРОДНОГО ПАРКА, КАЗАХСТАН) - Жумабекова , Б.К; Хамзина , Ш.Ш; Жексенова , Ж.С; Омаров , М.К. (Actual problems and prospects of the study of the fauna, 2024)
Bayanaul Nature Park serves as an important center for environmental education and conservation in Kazakhstan. The park promotes sustainable tourism, implements educational programs and environmental projects that raise visitors' awareness of the importance of protecting biodiversity, sustainable nature management, and preserving the region's unique ecosystems.